Fabrication and Thermal Degradation Kinetics of PBT/BEO/Nano-Sb2O3 Composites. (28th December 2020) - Ma, Meng; Niu, Lei; Ma, Jinming; Ma, Jiqiang; Jiao, Tifeng
Abstract : Developing polybutylene terephthalate (PBT) with high thermal stability and flame-retardant properties is crucial for automotive, biomedical devices, electronics, and other fields. Herein, we focus on a PBT/brominated epoxy resin (BEO)/nano-Sb2 O3 composites by a melt-blending method. The effects of heating rate and nano-Sb2 O3 content on the thermal stability and thermal degradation kinetics of PBT composites were studied by TG-DSC. With the increasing of heating rate, the thermal hysteresis effect of temperature gradient is produced, which is eliminated when the temperature exceeds 400°C. With the increase of nano-Sb2 O3 content, the E a of PBT/BEO/nano-Sb2 O3 composites increases at first and then decreases. When the content of nano-Sb2 O3 is 3 wt%, the E a of PBT/BEO/nano-Sb2 O3 is the highest, which is 66.18 kJ/mol (31.43%) higher than that of neat PBT. Also, the exploration of the thermal degradation kinetics of PBT/BEO/nano-Sb2 O3 composites is expected to provide research ideas for new high flame-retardant materials.